Indonesian EFL students’ reading motivation and writing achievement across gender - Ajeng Inayatul Ilahiyah; Diah Maya Andina; Punggulina Andawaty Tiven; Bambang Yudi Cahyono (EduLite: Journal of English Education, Literature and Culture, 2019)
The inseparable linkage between reading and writing has gained a crucial emphasis on language learning.  It has been regarded as a constructive issue for the improvement in teaching English skills. However, little attention is given to the underlying relationship between students’ motivation in reading and their achievement in writing.  This current research aimed at the correlation between students' reading motivation and their writing achievement across gender. It involved 50 third-year EFL students enrolled essay writing course divided into two classes in the ELT department. The quantitative data were collected through the use of the questionnaire on motivation in reading. Correlation analysis completed using Pearson product-moment revealed that the students' motivation in reading significantly positive influences their writing scores. It described that changes in students' reading motivation are a very weak correlation with the changes in their writing score. Another finding demonstrated that female and male students’ reading motivation and their writing achievement are significantly different. It signified that the differences correlation coefficient of both male and female students. Finding teaching implication is one of the areas that future researchers are suggested to investigate. Regarding the research findings, it indicates that there are more extensive areas offered for further studies in the relationship between reading and writing.